2010
DOI: 10.1097/aog.0b013e3181d56e12
|View full text |Cite
|
Sign up to set email alerts
|

Efforts Needed to Provide Institute of Medicine–Recommended Guidelines for Gestational Weight Gain

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…We are not aware of other studies that examined documentation of adherence to guidelines according to weight category, apart from a single study that examined only gestational weight gain and not the additional outcomes. This study, located in a Massachusetts tertiary care center, found even lower rates (only 4.6%) of documentation of pre-pregnancy BMI in the antenatal records [26]. …”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of other studies that examined documentation of adherence to guidelines according to weight category, apart from a single study that examined only gestational weight gain and not the additional outcomes. This study, located in a Massachusetts tertiary care center, found even lower rates (only 4.6%) of documentation of pre-pregnancy BMI in the antenatal records [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Height, weight, gestational weight gain, birth weight, and delivery gestational age have been previously validated. 1517 Data retrieved from the electronic medical record was supplemented by and validated with manual chart abstraction for delivery mode, cervical dilation, and fetal station. The University of Massachusetts Medical School Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…(10) However, up to 83% of obese pregnant women exceed these recommendations. (11-13) Given that most women are motivated to have “healthy pregnancies,” gestational weight gain (GWG) is potentially modifiable through behavioral interventions that target physical activity, nutrition, etc. Accordingly, the IOM report stated that interventions will be needed to assist obese women to meet the GWG goals.…”
Section: Introductionmentioning
confidence: 99%